Gastrointestinal Bleeding in Small Intestinal Stromal Tumors: A Clinicopathological and Survival Analysis - Fu, Fengqin; Pu, Hui; Huang, Weiping; Han, Lin; Deng, Yongbin; Lai, Yadong (Turkish Journal of Gastroenterology, 2025)
Background/Aims: This study analyzes the clinical pathological characteristics and prognostic factors of small intestinal stromal tumor (SIST) patients with gastrointestinal (GI) bleeding and investigates whether GI bleeding is an independent predictor of SIST prognosis. Materials and Methods: A retrospective analysis of 152 patients diagnosed with SISTs at Zhangzhou Municipal Hospital Affiliated to Fujian Medical University was conducted. Patients were divided into 2 groups based on the presence or absence of GI bleeding. Both survival and recurrence rates were calculated using univariate survival analysis and Cox regression analysis, respectively. Results: Compared with the non-GI bleeding group, the GI bleeding group showed significant differences in tumor rupture and Ki-67 abundance (P < .05). Survival analysis revealed that patients with GI bleeding had a shorter relapse-free survival (RFS) compared to those without GI bleeding (P = .016); however, GI bleeding significantly impacted RFS only in the high-risk group (P = .001). Cox regres sion analysis showed that mitotic count (P = .021), tumor rupture (P = .032), Ki67 positivity (P = .032), and GI bleeding (P = .04) were independent factors affecting the relapse-free survival rate of SISTs. Conclusion: This study shows that SIST patients with GI bleeding are more likely to experience tumor rupture and have higher Ki-67 positivity than those without GI bleeding. Mitotic count, tumor rupture, Ki-67 abundance, and GI bleeding are independent predictors of SIST prognosis. Additionally, the RFS rate for patients with GI bleeding is shorter, particularly among high-risk patients. Cite this article as: Fu FQ, Pu H, Huang WP, Han L, Deng YB, Lai YD. Gastrointestinal bleeding in small intestinal stromal tumors: A clinicopathological and survival analysis. Turk J Gastroenterol. Published online November 21, 2025. doi:10.5152/tjg.2025.25205.